PENINGKATAN AKTIVITAS SISWA DALAM PEMBELAJARAN IPS MENGGUNAKAN MODEL ROLE PLAYING DI SEKOLAH DASAR - Yoserizal, Yoserizal; Arwin, Arwin; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The study was aimed at describing the improvement of students’ activities in learning the Social Science subject by using Role Playing Model at 5th grade of  Sungai Geringging, Padang Pariaman. The subjects of the study were the teachers and 18 students of the school. The classroom action research was conducted in this research. The result of the research shows that the students’ activities increased from the first cycle to the second one: visual activity increased from 72.22% (adequate) in cycle I to 87.49% (very good) in cycle II; (b) oral activity increased from 71.17% (adequate) in cycle I to 86.45% (very good) in cycle II; (c) listening activity increased from 72.56% (adequate) in cycle I to 86.10% (very good) in cycle II; (d) metric activity increased from 72.22% (adequate) in cycle I to 86.8% (very good) in cycle II; (e) emotional activity increased from 73.61% (adequate) in cycle I to 86.8% (very good) in cycle II. This means that the Role Playing model is able to improve the students’ activities in learning The Social Science Subject. Keywords: The Social Sciens Subject , Role Playing Model